Foraging Behavior of Odontomachus bauri on Barro Colorado Island, Panama - Birgit Ehmer; Bert Hölldobler (Psyche: A Journal of Entomology)
Foraging behavior and partitioning of foraging areas of Odonomachus bauri were investigated on Barro Colorado Island in Panama. The activity of the ants did not show any daily pattern; foragers were active day and night. The type of prey captured by O. bauri supports the idea that in higher Odontomachus and Anochetus species, the high speed of mandible closure serves more for generating power than capturing elusive prey. Polydomous nests may enable O. bauri colonies to enlarge their foraging areas.